Effects of Rumex nervosus leaf powder supplementation on carcasses compositions, small intestine dimensions, breasts color quality, economic feasibility in broiler chickens - Mohammed M. Qaid; Saud I. Al-Mufarrej; Maged A. Al-Garadi; Ahmed A. Al-Haidary (Poultry Science, 2023)
ABSTRACT: Carcass characteristics, product quality, and the conversion of feed into meat with higher performance and feasibility are important determinants of the profitability and sustainability of any poultry enterprise. The objective of this study was to investigate the potential effect of Rumex nervosus leaf powder (RNLP) on carcass composition, small intestine dimensions, breast color quality, and economic feasibility of Ross broiler chickens. A total of 122 broilers were randomly distributed evenly among 4 treatments (0, 1, 3, and 5 g RNLP/ kg diet, n = 5 replicates per treatment, with 6 broilers per replicate: 3 ♀ and 3 ♂). Performance and economic data were collected in each replicate during the experiment. One male bird from each replication was examined for other criteria on d 34. Results showed that broilers fed 3 g of RNLP had a higher eviscerated carcass weight and dressing percentage (P < 0.05) than the control. The RNLP-fed broilers had higher weights and thicknesses in the duodenum and jejunum of up to 5 g and in the ileum and overall small intestine of up to 3 g. Broilers fed the lowest levels of RNLP had the highest revenue and net gain and the lowest cost–benefit ratio compared with those fed the highest levels of RNLP. The results indicate that the addition of RNLP has a positive effect on carcass processing, the intestinal measurements, and profitability ratios of the broilers. The 1 g RNLP/kg feed is the recommended dose to increase productivity and economic profitability ratios per kilogram of meat.